Craniofacial height in relation to cross-sectional maxillary and mandibular morphology - Anna Klinge; Karin Becktor; Christina Lindh; Jonas P Becktor (SpringerOpen, 2017)
Abstract Background In order to gain a better understanding of how growth of the alveolar bone is linked to the vertical development of the face, the purpose of this study was to investigate if there is an association between the cross-sectional morphology of the maxillary and mandibular bodies with the craniofacial height, using images from cone beam computed tomography (CBCT). Methods From 450 pre-treatment CBCT scans, 180 were selected to be included in the study. Lateral head images were generated from the CBCT scans and were used to categorise subjects into three groups based on their vertical craniofacial height. Cross-sectional images from CBCT volumes were reformatted of the maxillary and mandibular bodies at five locations in the maxilla and five in the mandible. Each image was measured at one height and two width measurements. Statistical analysis performed was the one-way analysis of variance with a Tukey post hoc test. A significance level of 5% was used in all comparisons. Results Patients with large vertical craniofacial height had a significantly higher cross-sectional area both in the maxilla and in the mandible. In the same group, the cross-sectional area was significantly thinner in the mandible compared with the other two groups, especially in the anterior region. Conclusions This study further highlights the close relationship between craniofacial height and alveolar bone dimensions and contributes with important knowledge for planning and follow-up of comprehensive dental- and orthodontic treatments.